Production system and breeding practice of indigenous chickens in selected districts of Dawro zone and Konta special district, Southern Ethiopia (Asian Journal of Agriculture, 2021)
Abstract. Melak A, Kenfo H, Aseged T, Hailu A. 2021. Production system and breeding practice of indigenous chickens in selected districts of Dawro zone and Konta special district, Southern Ethiopia. Asian J Agric 5: 72-83. This study was conducted to understand the production system, breeding practices, selection criteria, and production constraints of chickens to have a baseline for future production strategies in the study area. The data was collected through individual interviews, focus group discussions, and personal observations. A semi-structured questionnaire using Food and Agriculture Organization Guidelines was used to avail the views of the respondents. Based on chicken population, production potential, and road accessibility, a total of 90 households from six kebeles were considered for an individual interview. The data was analyzed using SPSS software version 23.0 and an index was calculated for all ranked variables like the importance of livestock, purpose of keeping chicken, selection criteria, culling criteria, and constraints of chicken production. The index value of meat production and income generation in midland agroecology were 0.28 and 0.26 respectively. Also, the index value of income generation and meat production in lowland agroecology were 0.31 and 0.25 respectively. It is concluded that both female and male chickens are maintained mainly for income generation followed by meat sources. A variable that was given a higher priority in breeding selection was body size and health conditions, for male and female chickens respectively. Most of the respondents select their breeding hen in health, egg production, and age with an index value of 0.44 and 0.36 and 0.15 respectively; while their breeding cock in body size, disease resistance, and color with an index value of 0.36, 0.29, and 0.28 respectively. Disease and predators were the major constraints of chicken production mentioned in the study area. Therefore, addressing these constraints is important to design a successful genetic improvement scheme.
Keywords: Constraints, Ethiopia, identification, indigenous chicken, selection criteria, trait preference